Pneumatic Artificial Muscle Based on Novel Winding Method - Disheng Xie; Zhuo Ma; Jianbin Liu; Siyang Zuo (Actuators, 2021)
This paper proposes a pneumatic artificial muscle based on a novel winding method. By this method, the inflation of silicone tubes is transformed to the contraction of muscle, whereas the expansion keeps on one side of the muscle, i.e., the expansion of the actuator does not affect the object close to it. Hence the muscle is great for wearable robots without squeezing on the user’s skin. Through necessary simplification, the contraction ratio model and force model are proposed and verified by experiments. The prototype of this paper has a maximum contraction ratio of 35.8% and a maximum output force of 12.24 N with only 5 mm thickness. The high compatibility proves it excellent to be the alternative for wearable robots.